Severity of Kratom (Mitragyna speciosa Korth.) Psychological Withdrawal Symptoms - Singh, Darshan; Narayanan, Suresh; Müller, Christian P.; Swogger, Marc T.; Rahim, Azlan Abdul; Bin Abdullah, Mohammad Farris Iman Leong; Vicknasingam, Balasingam K. (Journal of Psychoactive Drugs, 2018)
Kratom leaves (Mitragyna speciosa Korth.) are traditionally used in Southeast Asia for their medicinal value. Self-report studies suggest that cessation from chronic kratom tea consumption (freshly brewed kratom tea) was associated with unpleasant psychological symptoms. This study sought to assess the severity of anxiety and depression during kratom cessation. Regular kratom users (N = 150) were recruited from the northern state of Penang (Malaysia) for this retrospective study. The Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) scales were used to assess the severity of the symptoms of anxiety and depression. Most respondents (70%) experienced symptoms of mild anxiety, while 81% experienced symptoms of mild depression during kratom cessation. Those who consumed higher quantities of kratom tea daily (≥4 glasses) had higher odds of reporting longer duration of kratom use history (OR = 4.8, 95% CI 2.3 -10.1, p < 0.001), higher frequency of daily kratom use (≥4 times) (OR = 72, CI 9.5- 543.1, p < 0.001), and were more likely to experience moderate symptoms of depression (OR = 2.9, CI 1.1-7.3, p = 0.020) during kratom cessation than those who consumed between one and three glasses of kratom tea per day. Cessation from regular and long-term kratom tea consumption was not associated with symptoms of high anxiety or depression.
EVALuna2:211701